Pemahaman Membaca Siswa Pada Pembelajaran dengan Metode KWL - Hadi, Alfan (Universitas Hamzanwadi, 2024)
This study aims to determine the effect of Know-Want-Learn (KWL) method to improve students' reading comprehension. This type of research is a quasi-experiment design with One Group Pretest-Posttest Design. The samples in this study were all students of class IXA and IXB MTs. Attarbiyah Addiniyah Gersik Kediri West Lombok Study Year 2023/2024 which amounted to 52 students. Data collection methods in this study are as follows: reading comprehension ability rubric which consists of 4 aspects, namely the ability to capture the content of the reading, the ability to summarize the reading, the ability to answer questions based on the content of the reading, and the ability to retell the content of the reading the data analysis technique uses the paired sample t-test formula. Based on the results of data analysis and discussion in the study, it can be concluded that,